Measurement of accommodation response in integral photography images - Yano, Sumio; Imai, Hiromichi; Park, Min-Chul (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2018)
A method of displaying a multiview image set prepared by a computer on an electronic display device based on integral photography has been formulated. With the device, accommodation response was measured and the result that the accommodation response linearly changed within and outside the range of depth of focus was obtained. In contrast, in the measurement of the accommodation response using the stereoscopic image, the accommodation response showed a linear change within and outside the depth of focus at the spatial resolution of three cycle per degree (cpd) or less. Therefore, it can be considered that the measurement result of the accommodation response for integral photography with a spatial resolution of 3 cpd or less cannot be used to determine whether it is influenced by the integral photography display method or spatial resolution reduction. From these results, we found that spatial resolution is required to be 3 cpd or more when outside of the range of depth of focus in the measurement of the accommodation response for integral photography. (C) 2018 Society of Photo-Optical Instrumentation Engineers (SPIE)